Hubungan Dukungan Orang Tua Dan Sikap Pergaulan Remaja Terhadap Kejadian Pernikahan Dini : The Relationship Between Parental Support and Adolescents' Social Interaction Attitudes Toward the Occurrence of Early Marriage - Melyana, Intan; Ulfah, Bardiati; Daud, Izma; Suryati, Suryati (Chakra Brahmanda Lentera Institute, 2026)
Early marriage remains a health and social problem that affects adolescents’ reproductive health, psychological well-being, and prospects. Factors suspected to contribute to this issue include parental support and adolescents’ social behavior. Lack of parental support and negative social interactions may increase the risk of early marriage. This study used a quantitative, cross-sectional design. The sample consisted of 100 female adolescents aged 15–20 years, selected purposively. Data were collected using questionnaires and analyzed using the Chi-Square test at the 0.05 significance level. Most respondents had good parental support (70%) and positive social behavior (65%). However, the analysis showed no significant relationship between parental support and the incidence of early marriage (p = 0.124), nor between adolescents’ social behavior and early marriage (p = 0.199). There is no significant relationship between parental support and adolescents’ social behavior and the incidence of early marriage. Nevertheless, these factors still play an important role in shaping adolescents’ behavior, so continuous education and guidance from parents and healthcare providers are needed.